An evaluation of stock–recruitment proxies and environmental change points for implementing the US Sustainable Fisheries Act - Punt, André E.; Szuwalski, Cody S.; Stockhausen, William (Fisheries research, 2014)
•BMSY estimates are needed to manage Alaska crab fisheries.•Proxy methods for estimating BMSY are currently used for management.•Methods which use stock and recruitment data and allow for changes in productivity due to the environment are outlined. The US Sustainable Fisheries Act requires overfishing limits for all managed stocks and evaluations of whether stocks are in overfished status or subject to overfishing. Overfishing is defined relative to the exploitation rate corresponding to MSY, FMSY, while being in an overfished state relates to stock biomass relative to the biomass corresponding to MSY, BMSY. FMSY and BMSY are impossible to estimate for most US fish and invertebrate stocks. Consequently, management advice for Bering Sea and Aleutian Islands (BSAI) crab stocks is based on “proxies”, such as that FMSY is approximated by F35%. Furthermore, BMSY should be defined under prevailing environmental conditions, which implies using only past data under current environmental conditions to estimate BMSY. Assessments for five BSAI crab stocks are used to evaluate the estimates of BMSY from a variety of methods for calculating BMSY proxies. Analyses based on fitting stock–recruitment relationships to the estimates of recruitment and mature male biomass from these assessments suggest that the assumption FMSY=F35% is generally reasonable, but that the stock and recruitment data do not generally support the current BMSY values. Changes over time in average recruitment and in the form of the stock–recruitment relationship were found for most stocks. Of the methods considered, fitting stock–recruitment relationships and exploring whether they have changed over time appears the most promising approach. The dynamic B0 method also appears promising, but there is considerable uncertainty in BMSY values between harvest control rules, and assumptions regarding how recruitment is adjusted given changes in mature male biomass.